Evaluation of an Nd doping effect on characteristic properties of tin oxide. (February 2015) - Turgut, G.; Sonmez, E.; Duman, S.
Abstract: In the present work, transparent and conductive Nd doped SnO2 thin films were deposited via spray pyrolysis. Crystallographic, morphological, optical and electrical characterizations of SnO2 were researched as a function of Nd doping. The XRD analysis indicated the films had tetragonal cassiterite tin oxide structure and (211) preferential direction for NdTO-0, NdTO-1, NdTO-2 and NdTO-3 samples changed to (110) plane for NdTO-4 and NdTO-5 samples. The crystalline size and strain analysis were made by using a Williamson–Hall method. The SEM micrographs showed that all films had homogenously scattered pyramidal and small densely nanoparticles. The optical analysis indicated optical band gap value of undoped film increased with 1 at% Nd doping and then it decreased with more Nd content. The Hall measurements indicated that the highest electrical conductivity was obtained for 2 at% Nd doping content.